THE CURRENT AND FUTURE COMPLIANCE AREAS OF KERMES OAK (QUERCUS COCCIFERA L.) UNDER CLIMATE CHANGE IN TURKEY - Babalik, Ahmet Alper; Sarikaya, Oguzhan; Orucu, Omer Kamil (Parlar Scientific Publications (P S P), 2021)
Modeling the niches and distributions of the species using machine learning technique has become one of the effective tools of conservation planning today. Analyzing how the main species of our country will be affected by climate change is of great importance for planning about these species. Quercus coccifera which is one of the important evergreen oak species in Turkey, is easily selected by goats and constitutes a high proportion of their diets. In this study, it is aimed to determine the potential distribution area of Quercus coccifera and how it will be affected by climate change. Bioclimate layers with a resolution of approximately 1 km(2) (30 arc seconds) obtained from the WorldClim database with the presence data of the species were cut within the specified limits and processed with the Maximum Entropy algorithm to determine the potential distribution area of the species in today's conditions. In addition, the potential distribution area in 2050 and 2070 was modeled according to the climate scenarios in RCP 2.6, RCP 4.5, RCP 6.0 and RCP 8.5 in order to determine how the distribution area of the species will be affected by climate change. According to the CCSM4 climate change scenario, it is seen that there are losses in potential distribution areas of the species in the future. The result of the study shows that the current and future spread areas of Quercus coccifera, which is spread in a very limited area, will gradually narrow.
Keywords: Quercus coccifera; climate change; potential distribution; Turkey; MaxEnt